Peran Kepala Madrasah dalam Mengelola Siklus Perencanaan Pendidikan Tahunan (RKT) dan Lima Tahunan (RENSTRA) - Sriati, Sriati; Syafi’i, Muhammad (Lembaga Yasin AlSys, 2026)
Educational planning through strategic documents has long been recognized as an essential instrument for quality improvement; however, empirical studies on how school principals manage the planning cycle through the Strategic Plan (Rencana Strategis, Renstra) and Annual Work Plan (Rencana Kerja Tahunan, RKT) remain limited. This study aims to examine the role of the madrasah principal in managing the educational planning cycle through the Renstra and RKT as instruments for improving educational quality at MTsN 8 Jombang. The study employed a Research and Development (R&D) method with a qualitative approach, with data obtained through interviews with the madrasah principal, vice principals, and the madrasah development team, as well as analysis of planning documents. The findings show that the principal plays an active role in initiating the preparation of the Renstra, setting policy directions, and ensuring alignment between medium-term planning and annual operational planning. The implementation of the Renstra and RKT was carried out systematically through cross-unit coordination, strengthening of teacher professionalism, and continuous performance-based evaluation. The study concludes that effective management of educational planning requires strategic leadership capable of integrating planning, implementation, and evaluation in a sustainable manner as a prerequisite for improving madrasah quality.